2008
DOI: 10.1523/jneurosci.1097-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Amygdaloid Injection of Kainic Acid in Rats with Genetic Absence Epilepsy: The Relationship of Typical Absence Epilepsy and Temporal Lobe Epilepsy

Abstract: We showed previously that genetic absence epilepsy rats from Strasbourg (GAERS) resist secondary generalization of focal limbic seizures after electrical kindling. We now investigate the effect of intra-amygdaloid injection of kainic acid, as another model of temporal lobe epilepsy, focusing on epileptogenesis, spike-and-wave discharges (SWDs), and the transition from basal to SWD states in GAERS. The EEG was recorded from the hippocampus and cortex of adult GAERS and Wistar rats before kainic acid injections … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 44 publications
2
31
0
Order By: Relevance
“…On the other side, absence animal models of epilepsy, such as WAG/Rij and GAERS rats, are resistant to amygdaloid kindling (Onat et al, 2007) and the demonstration that suppression of absence seizures by intracortical injection of ethosuximide reduces the resistance to kindling also supports a correlation between thalamo-cortical alterations and amygdala (Gülhan Aker et al, 2010). Furthermore, a not defined correlation between absence seizures and temporal lobe epilepsy has been previously demonstrated by injecting kainic acid into the amygdala of GAERS (Gurbanova et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…On the other side, absence animal models of epilepsy, such as WAG/Rij and GAERS rats, are resistant to amygdaloid kindling (Onat et al, 2007) and the demonstration that suppression of absence seizures by intracortical injection of ethosuximide reduces the resistance to kindling also supports a correlation between thalamo-cortical alterations and amygdala (Gülhan Aker et al, 2010). Furthermore, a not defined correlation between absence seizures and temporal lobe epilepsy has been previously demonstrated by injecting kainic acid into the amygdala of GAERS (Gurbanova et al, 2008).…”
Section: Discussionmentioning
confidence: 85%
“…However, the EEG correlates of these spasms, despite variable morphological characteristics, are almost always a generalized paroxysmal discharge, even in patients with hemihypsarrhythmia [17]. A delayed effect of generalized epilepsy on the onset of experimental focal seizures in some studies on adult rats with genetically determined deficiencies was reported previously [18,19]. Here, the situation was the opposite, suggesting that the focal firing can produce a delayed effect on the maturational processes including myelination, which are necessary for generalization of epileptic discharges.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, genetic epileptic WAG/Rij rats have also clear low frequency delta activity prior to the onset of SWDs in cortex and thalamus [50]; it is also likely that synchronized activity in cortex and thalamus builds up or reduces before SWD onset, rather than being a sudden generalized synchronous event. The latter has also been proposed in WAG/ Rij rats based on outcomes of classical FFTs, NA analyses, and wavelet analyses [14,28,43]. However, the current study is a preliminary study and it needs to be assessed with a larger data set.…”
Section: Discussionmentioning
confidence: 99%